(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is dedicated to cultivating skills for the effective utilization of modern information resources. It examines various types of information resources—such as the Internet, electronic libraries, social networks, and digital tools—as well as methods for their use and strategies to develop these competencies. Special attention is given to verifying information reliability, using search engines efficiently, managing time, and fostering critical thinking. These skills are crucial for personal and professional growth, helping individuals navigate the flow of information effectively.